Dawr al-Juhūd al-Rasmīyah wa-al-ʻUlamāʼīyah (al-ʻUmānīyah wa-al-ʻArabīyah) fī Ṭibāʻat al-Turāth al-ʻUmānī - ʻAlī, Ajqū (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
The invention of printing with movable type by the German Gutenberg led to an unmatched revolution in the printing and publication of books, reckoned the principal gateway to the modern European renaissance. The history of printing in Arabic letters did not begin in the Arab world but in Europe, where the first book in Arabic was printed in Germany in 1468 by the monk Martin Roth, a Christian religious work. The printing movement of which the West was the stage found its way to the Arab world only at the beginning of the eighteenth century, for several reasons: in Syria the first press appeared in 1706 and in Lebanon in 1734, after which presses spread in many Arab countries, though never rising to what the early pioneers had hoped for. In Oman the first press appeared later still, and this paper traces the official and scholarly efforts, Omani and Arab alike, that brought the Omani heritage into print.
MHF-PRINT2018-030
Keywords: History of printing; Arabic typography; Omani heritage; Scholarly efforts; Publishing institutions; Book history